Growth and Survival Evaluation of Oreochromis Sp fed Hermetia illucens Larva and Manihot esculenta leaves Meal - Nur Aini; Rudy Agung Nugroho; Nova Hariani (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
This study was conducted to compare the effects of dietary substitution of fish meal (FM) with black soldier fly (Hermetia illucens) larvae meal (BSFM) and Manihot esculenta leaves meal (MEM) on the growth and feed efficiency of Oreochromis sp. Four concentrations viz: P1 (25%): 50g BSFM and 25g MEM, P2 (50%): 100g BSFM and 50g MEM, P3 (75%): 150g BSFM and 75g MEM, P4 (100%): 200g BSFM and 100g MEM were prepared and tested against control without FM replacement. Each diet was fed to three replicates groups of fish at a rate of 5% of body weight two times per day for 30 days. At the end of the trial, growth parameters, Feed conversion rate (FCR), and feed efficiency (FE) were evaluated. The results showed that fish fed dietary substitution of FM with combination ratio of BSFM and MEM higher than 50% significantly improved all growth parameters, FCR and FE. It is therefore suggested that the partial (higher than 50%) or total replacement of fish meal with combination of BSFM and MEM in the diet of Oreochromis sp can be used as fish meal substitution to obtain better growth and feed efficiency.